Case Report: Clinical Experience With Avelumab in Patients With Metastatic Merkel Cell Carcinoma and Brain Metastases Treated in Europe - Fife, Kate; Tétu, Pauline; Prabhakaran, Jessica; Lebbé, Celeste; Grignani, Giovanni (Frontiers in Oncology, 2021)
Merkel cell carcinoma (MCC) is a rare and aggressive skin cancer that can metastasize rapidly. In patients with metastatic MCC (mMCC), brain metastases are uncommon but are associated with poor prognosis; furthermore, there is limited published literature regarding treatment of these patients, and no specific regimens are currently recommended by guidelines. Avelumab, an anti–programmed death ligand 1 monoclonal antibody, was the first approved treatment for patients with mMCC. Here, we present 4 cases of patients with mMCC and brain metastases treated with avelumab. Patient age ranged from 48 to 70 years, and all patients received avelumab as second-line therapy following disease progression with platinum-based chemotherapy. Patient cases 1 and 2 received avelumab alone and experienced rapid disease progression according to Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST 1.1). In patient case 3, avelumab alone resulted in a prolonged complete response by RECIST 1.1 of 1 brain metastasis and partial response by RECIST 1.1 of a second brain metastasis. After 11 months of avelumab treatment, the patient received concurrent stereotactic radiosurgery that resulted in complete response of the second metastasis. Patient case 4 achieved a complete response by RECIST 1.1 with avelumab plus stereotactic radiosurgery. These results suggest that avelumab followed by radiotherapy or with concurrent radiotherapy may be an effective treatment option for patients with mMCC and brain metastases.